(untitled) (Research, Society and Development, 2021)
This research aimed to evaluate the reliability of methods using a new graphic template to evaluate alveolar bone graft in cleft lip palate on radiographs. The sample consisted of 30 radiographs of individuals with bone grafts that were analyzed by two raters using SWAG and Chelsea, alveolar bone graft rating methods. The images were analyzed in PowerPoint, and second, introducing a template, that was designed in PowerPoint by the examiners. The inter-reliability and intra-reliability were determined using weighted Kappa statistics, with and without the template, in Jamovi 1.2 software. The determination of the intra-reliability was performed through the random selection of 10 radiographs. Inter-rater reliability in SWAG and Chelsea methods without the template, were moderate (0.574 and 0.519) and with was good (0.745 and 0.735) in both scales. Intra-rater reliability was good (0.710-0.610 and 0.634-0.639) in SWAG and Chelsea methods without the template, and including, this reliability was very good (1 and 0.846) in SWAG scale and good to very good (0.872 and 0.762) in Chelsea method. The use of a template to evaluate the images of alveolar bone grafts in both methods had a positive impact on the results, increasing inter-rater to good and intra-rater reliability to very good.